Investigation of accuracy and dimensional limits of part produced in aluminum alloy by selective laser melting. Issue 1 (January 2017) - Calignano, F.; Lorusso, M.; Pakkanen, J.; Trevisan, F.; Ambrosio, E.; Manfredi, D.; Fino, P.
Abstract Selective laser melting (SLM) process, an additive manufacturing (AM) technology, has had a rapid growth in the biomedical and aerospace markets because of the ability to manufacture complex designs directly from computer-aided design (CAD) using materials such as titanium and aluminum alloys. Although this technology allows designers to fabricate geometries not achievable with conventional manufacturing, it has some restrictions. The paper presents the technological problems and restrictions resulting in the production of structures in aluminum alloy by SLM. In particular, it analyzed the input file of the process, .STL file, and the dimensional limits of geometries with sharp edges as a simple parallelepiped with a square base since the understanding of the limitations can help the designer in the creation of new components. The creation of function-independent design rules, easily transferrable on individual part designs, could allow a wide industrial usage and a better knowledge of AM technologies. The results presented in this paper showed that the choice of parameters of conversion from the CAD model to .STL file could be a restriction for the software for preprocessing part but also affects the surface roughness. Moreover, if a SLM machine with a laser beam of 100 μm is used, it is not possible to produce geometries with sharp edges with size base below 0.8 mm in an aluminum alloy.